THE USE OF LOCKING SCREWS TO INCREASE THE RELIABILITY OF FASTENING THE CUTTING INSERTS OF FACE MILLING CUTTERS - Кушніров, Павло; Орлов, Роман; Гриценко, Олександр; Скабенок, Микита (SWorldJournal, 2024)
The paper considers designs of the face milling cutters in which cylindrical cutting inserts are fixed with fastening screws. The fastening mechanisms for cutting inserts also contain additional locking screws. As a result, the reliability of fastening t